A companion to Byzantine poetry
1 online resource.
Keywords: This book offers the first complete overview of Byzantine poetry from the 4th to the 15th century. By bringing together 22 scholars, it explores the development of poetic trends and the interaction between poetry and society throughout the Byzantine millennium; it addresses a wide range of issues concerning the writing and reading of poetry (such as style, language, metrics, function, and circulation); and it surveys a large number of texts by looking closely at their place within the social and cultural milieus of their authors. Overall, the volume aims to enhance our understanding of Byzantine poetry and shed light on its important place in Byzantine literary culture. Contributors are Eirini Afentoulidou, Gianfranco Agosti, Roderick Beaton, Floris Bernard, Carolina Cupane, Kristoffel Demoen, Ivan Drpic, Jürgen Fuchsbauer, Antonia Giannouli, Martin Hinterberger, Wolfram Hörandner, Elizabeth Jeffreys, Michael Jeffreys, Marc Lauxtermann, Ingela Nilsson, Emilie van Opstall, Andreas Rhoby, Kurt Smolak, Foteini Spingou, Maria Tomadaki, Ioannis Vassis, Nikos Zagklas.